Isolation, phenotyping and genotyping of listeria monocytogenes from food and wet markets in Kuching and Samarahan divisions, Sarawak - Wan Adnawani, Meor Osman (2007)
In this study, occurrence of Listeria spp., especially Listeria monocylogenes was determined in 440 food samples (poultry, beef and seafood) and 447 of tabletop samples from 11 wet markets in Kuching and Samarahan district, Sarawak. Two enrichment broths; Buffered Listeria Enrichment Broth and Fraser Broth were used in the isolation of L. monocylogenes followed by plating on selective PALCAM agar. Suspected colonies (black with grey-green zone) were picked and then streaked on the CllROMagar Listeria, a chromogenic medium for detection and isolation of L monocylogenes from other Listeria spp. A total of' 82 isolates were identified as L. monocylogenes by the formation of blue colonies with white halo on this agar. All positive isolates were confirmed using species-specific PC R. Based on the presence of the hlyA gene, the 82 isolates were confirmed as L. monocytogenes. The result showed 16 (3.6%) of the food samples and 11 (2.5%) of' the tabletop samples were positive for the occurrence of L. monocytogenes. This revealed a low occurrence of L. monocylogene. s in food and tabletop samples. All 82 isolates were further studied to determine their antibiotic resistance and occurrence of plasmid. L. monocvlogenes isolates were resistant to most antibiotics tested (nalidixic acid (100%), streptomycin (95.1%), ceftriaxone (89%), vancomycin (36.6%), chlorampenicol (12.2%), methacillin (12.2%), gentamicin (11%). kanamycin (8.5%), cephalothin (7.3%). tetracycline (7.3%) and erythromycin (3.7%)). However, all isolates were susceptible towards 3 antibiotics; ampicillin, hacitracin and carbenicillin. None of the L. monocivogencs isolates harboured plasmid. The results of' antibiotyping and plasmid profiles showed that no relationship could he established between the isolates. Screening for presence of the virulence genes (inWA gene, i(q) gene, pr/A gene and picA gene), 60 isolates were selected from food (30) and tabletop (30) samples. All the isolates tested showed positive results for the presence ofiap gene and pr1A gene.